ANALYSIS OF FACTORS AFFECTING THE PROFIT AND PROFITABILITY OF COMMERCIAL BANKS - Eshnazarov Ohunjon G'olibjon o'g'li (Scholar Express Journals, 2023)
This article aims to delve into the multifaceted factors that influence the profit and profitability of commercial banks. By employing a comprehensive approach, the study investigates key variables, employs various methods, and presents results to provide insights into the intricate dynamics shaping the financial performance of these institutions. The findings contribute to a nuanced understanding of the challenges and opportunities in the banking sector, offering valuable implications for stakeholders and policymakers.
Keywords: Commercial banks; Profit; Profitability; Financial performance